PREPARAÇÃO E CARACTERIZAÇÃO DE FILMES AUTOMONTADOS CONTENDO POLIELETRÓLITOS INORGÂNICOS E GOMA NATURAL DO CAJUEIRO. - Intema, Rolf de Campos (2011)
Nanocomposites in the form of ultrathin films with bilayer and tetralayer structure using the polyelectrolyte chloride 3-n-propyl-1-azonia-4-azabicyclo [2.2.2] octane silsesquioxane (designated as SiDb+Cl-) or polyelectrolyte chloride 3-n-propylpyridinium silsesquioxane (designated as SiPy+Cl-) and tetrasulfonated nickel phthalocyanine (NiTsPc), together with a natural polysaccharide, were produced using the Layer-by-Layer (LbL) technique on a FTO substrate (tin oxide doped with fluorine). The formation of the films was monitored by UV-VIS spectroscopy, accompanying the Q band of phthalocyanine. It was observed that for all the films studied that the absorbance of the Q band at 620 nm linearly increased with the number of bilayers indicating that the same amount of material is adsorbed to each bi/tetralayers prepared. It was also observed that the spectra of the films (SiPy+Cl-/Goma/SiPy+Cl-/NiTsPc) and SiDb+Cl /Goma/SiDb+Cl-/NiTsPc), the bands related to the monomeric species were more intense when compared to the films obtained without gum, which s an indication that the inclusion of the gum between the layers of the films can proportionate more organized films with higher interaction between the polymeric species. FTIR spectra showed a shift in the band referring to the NiTsPc sulfonic groups indicating that an electrostatic interaction occurs between NiTsPc and the polycations studied. AFM images showed up the interaction between the polycations of the film, which can be notice by the decrease on the films roughness with the increase of the number of bilayers. In this case, when comparing the SiDb+Cl- containing films with SiPy+Cl- ones, it was observed a more considerable decrease in the rugosity values for the SiPy+Cl- films. Results of cyclic voltammetry carried out with these films with architectures (SiPy+Cl-/Goma/SiPy+Cl-/NiTsPc), (SiPy+Cl- /NiTsPc), (SiDb+Cl-/Goma/SiDb+Cl-/NiTsPc) and (SiDb+Cl-/NiTsPc) showed a peak related to the aromatic ring of NiTsPc at 1.4 V. The stability as a function of the number of the voltammetry cycles of the electrodes modified with SiPy+Clwas considerably greater than for the SiDb+Cl- films. These films were sensitive to DA detection at different concentrations in a range of 9.9.10-6 molL-1 to 9.1.10-5 mol L-1 with a detection limit of 7.72.10-6 mol L-1 and 8.34.10-6 molL-1 for architectures (SiPy+Cl-/NiTsPc) and (SiPy+Cl-/Goma/SiPy+Cl-/NiTsPc), respectively.